Respuesta :

Let's solve your equation step-by-step.5(x−6)=2(x−9)Step 1: Simplify both sides of the equation.5(x−6)=2(x−9)Simplify: (Show steps)5x−30=2x−18Step 2: Subtract 2x from both sides.5x−30−2x=2x−18−2x3x−30=−18Step 3: Add 30 to both sides.3x−30+30=−18+303x=12Step 4: Divide both sides by 3.3x/3=12/3x=4Answer:x=4

You had 2 equal signs in the equation. Solution 1 assuming "-"
Now assuming the "+" sign.

Let's solve your equation step-by-step.5(x−6)=2(x+9)Step 1: Simplify both sides of the equation.5(x−6)=2(x+9)Simplify: (Show steps)5x−30=2x+18Step 2: Subtract 2x from both sides.5x−302x=2x+182x3x−30=18Step 3: Add 30 to both sides.3x−30+30=18+303x=48Step 4: Divide both sides by 3.3x/3=48/3x=16Answer:x=16